2005
DOI: 10.1021/jp053517b
|View full text |Cite
|
Sign up to set email alerts
|

Metathesis Activity and Properties of Mo−Alkylidene Sites Differently Located on Silica. A Density Functional Theory Study

Abstract: Ethene metathesis proceeding on Mo-methylidene centers on silica is investigated with density functional theory, applying the cluster approach. Three different locations of the active sites are considered, in which the Mo center replaces a pair of geminal silanols, two silanols from adjacent geminal pairs and two single silanols, respectively. It is shown that metathesis activity of the Mo-methylidene sites strongly depends on their location on silica. Different reactivity of the centers toward alkene is expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 98 publications
8
52
0
1
Order By: Relevance
“…The first structure (1) was previously shown to be a reasonable model of the active site, on the basis of the comparison between the theoretical and experimental results [29]. The present model 1 and the corresponding structure from the Ref.…”
Section: Computational Detailsmentioning
confidence: 74%
See 3 more Smart Citations
“…The first structure (1) was previously shown to be a reasonable model of the active site, on the basis of the comparison between the theoretical and experimental results [29]. The present model 1 and the corresponding structure from the Ref.…”
Section: Computational Detailsmentioning
confidence: 74%
“…The present model 1 and the corresponding structure from the Ref. 29 differ from each other in the orientation of the hydroxyl group bonded to the Si2 atom. In the models 1-4, the Mo-methylidene center is attached to the silica cluster by replacing a pair of geminal silanols.…”
Section: Computational Detailsmentioning
confidence: 77%
See 2 more Smart Citations
“…Supported molybdenum oxide catalysts have been studied for numerous reactions like partial oxidation reactions of alcohols [1,2], ethers [3], alkanes and olefins [4][5][6], metathesis reactions [7,8] and the selective catalytic reduction (SCR) of nitric oxide [9,10]. Previous studies have shown that the catalytic properties may depend on the molybdenum oxide structure as well as the choice of the support material [3,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%